The Evolving Role of the Multidisciplinary Heart Team in Aortic Stenosis - Sahoor Khan; William Shi; Tsuyoshi Kaneko; Suzanne J Baron (US Cardiology Review, 2022)
Transcatheter aortic valve replacement has transformed the paradigm of care for patients with severe aortic stenosis (AS). With transcatheter aortic valve replacement now commercially approved for AS patients of all surgical risk, clinical decision-making regarding the initial mode of valve replacement (e.g. surgical versus transcatheter) and prosthesis type has become even more complex. The updated American College of Cardiology/American Heart Association and European Society of Cardiology/European Association for Cardio-Thoracic Surgery guidelines on valvular heart disease offer a strong foundation from which to address the nuances of the treatment of AS; however, there remain several clinical scenarios for which evidence and thus definitive societal recommendations are lacking. As such, the heart team continues to play an invaluable role in the management of the AS patient by combining available scientific evidence, expertise across disciplines, and the patient’s preferences to optimize individualized patient care and healthcare resource usage.